Free and Immobilized Microbial Culture–Mediated Crude Oil Degradation and Microbial Diversity Changes Through Taxonomic and Functional Markers in a Sandy Loam Soil - Khandelwal, Ashish; Sugavanam, Ramya; Ramakrishnan, B.; Dutta, Anirban; Varghese, Eldho; Nain, Lata; Banerjee, Tirthankar; Singh, Neera (Frontiers in Environmental Science, 2022)
Crude oil contamination of soil and water resources is a widespread issue. The present study evaluated the degradation of aliphatic hydrocarbons (C11–C36) in crude oil by 17 bacteria isolated from a crude oil–contaminated soil. The results suggested that Pseudomonas sp. and Bacillus amyloliquefaciens were the best hydrocarbon-degrading bacteria in the presence of surfactant Tween-80 (0.1% w/v). Based on the present investigation and a previous study, Pseudomonas sp. + B. amyloliquefaciens and fungus Aspergillus sydowii were identified as best oil degraders and were immobilized in alginate–bentonite beads, guargum–nanobenonite water dispersible granules (WDGs), and carboxy methyl cellulose (CMC)–bentonite composite. Sandy loam soil was fortified with 1, 2, and 5% crude oil, and total petroleum hydrocarbon (TPH) degradation efficiency of free cultures and bio-formulations was evaluated in sandy loam soils. Compared to a half-life (t1/2) of 69.7 days in the control soil (1% oil), free cultures of Pseudomonas sp. + B. amyloliquefaciens and A. sydowii degraded TPH with t1/2 of 10.8 and 19.4 days, respectively. Increasing the oil content slowed down degradation, and the t1/2 in the control and soils inoculated with Pseudomonas sp. + B. amyloliquefaciens and A. sydowii was 72.9, 14.7, and 22.2 days (2%) and 87.0, 23.4, and 30.8 days (5%), respectively. Supplementing soil with ammonium sulfate (1%) enhanced TPH degradation by Pseudomonas sp. + B. amyloliquefaciens (t1/2–10 days) and A. sydowii (t1/2–12.7 days). All three bio-formulations were effective in degrading TPH (1%), and the t1/2 was 10.7–11.9 days (Pseudomonas sp. + B. amyloliquefaciens and 14–20.2 days (A. sydowii) and were at par with free cultures. Microbial diversity analysis based on taxonomic markers and functional markers suggested that the bioaugmentation process helped keep soil in the active stage and restored the original microbial population to some extent. The present study concluded that bio-formulations of crude oil–degrading microbes can be exploited for its degradation in the contaminated environment.